Salivary microRNAs (hsa-miR-200a, hsa-miR-125a and hsa- miR-93) in relation to age, gender and histopathological parameters. - Shaimaa H Mudhir; Raja H Al-Jubouri; Ban A Abdul Majeed (Journal of Baghdad College of Dentistry, 2014)
Background: MicroRNAs (miRNAs) are small noncoding RNAs that post‐transcriptionally regulate gene expression by targeting specific mRNAs. The main objective of this study was measure the level of salivary (hsa-miR-200a, hsa-miR-125a and hsa- miR-93) in both oral squamous cell carcinoma and healthy controls to asses the association of them with age, gender and tumor grade materials and methods The level of three salivary microRNAs namely hsa-miR-200a, hsa-miR-125a and hsa- miR-93 were measured in saliva of patients with oral squamous cell carcinoma and healthy controls by using reveres transcription, preamplification and quantitative PCR also the general information from each patient including the age, sex and tumor grade were recorded. Results: Salivary miR-200a was down regulated while miR-93 was up regulated in saliva of females with OSCC compared to females of healthy control, also there was a weak and statistically insignificant positive linear correlation between tumor grade and hsa-miR-200a CT values (r=0.223).However each tumor grade group had a mean normalized CT value which was higher than that of controls with statistically significant differences, P